2016
DOI: 10.4314/jfas.8vi2s.6
|View full text |Cite
|
Sign up to set email alerts
|

Palladium induced oxidative stress and cell death in normal hepatocytes

Abstract: Palladium (Pd) accumulates in many organs and renders many deleterious effects. Although the Pd toxicity has been documented, the precise mechanism of Pd toxicity still needs to be elucidated. In the current research, a hepatotoxicity mechanism of Pd has been investigated.Our findings clearly indicate that Pd induces reactive oxygen species (ROS) formation and oxidative stress, mitochondrial and lysosomal injury and finally cell death. These effects are reversed by antioxidants and ROS scavengers, mitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…4 Shahraki et al have suggested that palladium-induced oxidative stress can potentiate lysosomal membrane permeability and thereby induce cytotoxicity. 5 Therefore, the development of effective methods for detecting palladium species in lysosomes is important for the early diagnosis of related diseases and studying the toxicity of palladium at the subcellular level.…”
Section: Introductionmentioning
confidence: 99%
“…4 Shahraki et al have suggested that palladium-induced oxidative stress can potentiate lysosomal membrane permeability and thereby induce cytotoxicity. 5 Therefore, the development of effective methods for detecting palladium species in lysosomes is important for the early diagnosis of related diseases and studying the toxicity of palladium at the subcellular level.…”
Section: Introductionmentioning
confidence: 99%